Growing Together: A Birthday Planting Pledge to Nurture Environmental Responsibility in Kids for a Greener Earth - Chavan, sangram Bhanudas; Halli, HM; Basavaraj, PS; Harisha, CB; boBoraiah, KM (Indian Journal of Agroforestry, 2025)
Deforestation has significantly reduced global tree cover, impacting biodiversity and climate resilience. While India has a long tradition of tree planting, rapid urbanization threatens its green cover. This paper proposes a simple yet impactful solution—encouraging children to plant and nurture trees on their birthdays. With over 63.4 million children in the 0-14 age group, this initiative could add billions of trees over time, aligning with India's Mission LiFE and afforestation goals. Inspired by successful community efforts like Piplantri’s girl child tree-planting tradition, this approach fosters environmental responsibility and complements government initiatives. Effective implementation requires post-planting care, school-led afforestation, and policy support to ensure long-term sustainability.